Video zipper: Energy saving techniques to compress video using motion prediction - Asral Bahari, Jambek, Dr.; Mohamad Halim, Abd Wahid, Dr.; Ahmad Husni, Mohd Shapri (Korea Invention News, 2013)
Cyber International Genius Inventor Fair (CIGIF) 2012, 3rd - 9th November 2012 was held at ChungMu Art Hall Convention Centre, Seoul, Korea.